Peningkatan Literasi Kesehatan Melalui Telenursing Dalam Mengatasi KEK Ibu Hamil - Gani, Nurul Fadhilah; Awaliyah, Rabiyatul; Nurhidayah, Nurhidayah; Hasnah, Hasnah; Annas, Jumrana; Mildawati, Titi (An Idea Health Journal, 2025)
Pregnancy constitutes a component of the broader human reproductive process. A salient issue during pregnancy is chronic energy deficiency (CED), defined as a condition in which an individual manifests nutritional deficiencies (calories and protein) that persist over an extended duration or are characterized as chronic. This condition can lead to various health complications for both mother and fetus, including an increased risk of low birth weight (LBW), miscarriage, premature birth, congenital disorders, small head size in newborns, maternal and infant mortality, difficult labor, postpartum hemorrhage, and cesarean section (CS) delivery due to mother's condition, which often results in a lack of energy to undergo a normal childbirth. The objective of this study is to ascertain the efficacy of telenursing in enhancing health literacy among pregnant women grappling with CED. This article utilizes a case study approach, employing instruments to assess the knowledge level of pregnant women and their nutritional status. The intervention strategy employed to address CED involves some improvement in health literacy through telenursing. The measurement of knowledge level and nutritional monitoring were carried out over a period of 14 days. The findings indicate that clients exhibited an enhancement in knowledge levels following the provision of health literacy and nutrition education. Furthermore, the study found that pregnant women were able to effectively manage their nutritional needs during pregnancy. The efficacy of telenursing in improving health literacy concerning nutritional needs among pregnant women susceptible to CED is substantiated by this study. Thus, it is recommended that frontline health workers consider utilizing telenursing in healthcare services, particularly in providing education and support for pregnant women, as a strategic approach to addressing Chronic Energy Deficiency (CED) during pregnancy